2000
DOI: 10.1007/3-540-46430-1_36
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Invariance of Discrete Time Systems

Abstract: Abstract. An algorithm for computing the maximal controlled invariant set and the least restrictive c o n troller for discrete time systems is proposed. We show h o w the algorithm can be encoded using quantier elimination, which leads to a semi-decidability result for de nable systems. For discrete time linear systems with all sets speci ed by l i near inequalities, a more e cient implementation is proposed using linear programming and Fourier elimination. If in addition the system is in controllable canonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…These three operations are easily implemented for LTI systems subject to linear inequality constraints [2,6,7,8,10,14]. Though the algorithms presented in this paper are difficult to implement for general nonlinear systems, there exist some classes of nonlinear systems for which the building blocks already are in place, such as piecewise affine systems and some classes of hybrid systems [1].…”
Section: Algorithm 21 (Controllable Sets) the Controllable Sets Of mentioning
confidence: 99%
See 1 more Smart Citation
“…These three operations are easily implemented for LTI systems subject to linear inequality constraints [2,6,7,8,10,14]. Though the algorithms presented in this paper are difficult to implement for general nonlinear systems, there exist some classes of nonlinear systems for which the building blocks already are in place, such as piecewise affine systems and some classes of hybrid systems [1].…”
Section: Algorithm 21 (Controllable Sets) the Controllable Sets Of mentioning
confidence: 99%
“…Though the algorithms presented in this paper are difficult to implement for general nonlinear systems, there exist some classes of nonlinear systems for which the building blocks already are in place, such as piecewise affine systems and some classes of hybrid systems [1]. Some work on developing algorithms for computing robust control invariant sets for hybrid systems has also been carried out by the authors of [14].…”
Section: Algorithm 21 (Controllable Sets) the Controllable Sets Of mentioning
confidence: 99%
“…In contrast, the computation of the maximal controlled invariant sets is recursive [3], [10]. Since controllable invariants are also controlled invariants, we could use the approach of this section for a nonrecursive computation of controlled invariants.…”
Section: Proposition 42 Xmentioning
confidence: 99%
“…The computation involves linear programming and projections (also known as FourierMotzkin eliminations). Related approaches have been used in [5], [10] for predecessor operator computations, in [3], [11] for the computation of the maximal controlled invariant set, and also in other contexts, e.g. [4], [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in control theory, projection is required for reachability analysis [1] and in decision theory for the elimination of existential quantifiers [2]. It can be shown that the calculation of affine maps or Minkowski sums of polyhedra are both polynomially equivalent to orthogonal projection [3,Sect.…”
Section: Introductionmentioning
confidence: 99%